Shear bond strength evaluation of metallic brackets bonded to a CAD/CAM PMMA material compared to traditional prosthetic temporary materials: an in vitro study - Gonzalo Andrés Garcés; Victor Hugo Rojas; Cristian Bravo; Camila S. Sampaio (Dental Press Editora, 2020)
ABSTRACT Introduction: Orthodontic treatment for adults is currently increasing, and therefore the need to bond brackets to restorations and temporary crowns. The use of CAD/CAM PMMA provisional restorations for orthodontic purposes have not yet been described, and there is currently insufficient information regarding the strength of bracket adhesion. Objective: This study aimed at evaluating the effects of thermocycling (TC) and surface treatment on shear bond strength (SBS) of brackets to different provisional materials. Methods: Forty specimens were made from each material [PMMA (Telio Lab), bis-acryl (Telio CS C&B), and PMMA CAD/CAM (Telio CAD)], sandpapered, and divided according to surface treatment (pumiced or sandblasted) and TC (half of the samples = 1,000 cycles, 5°C/55°C water baths) (n = 10/group). Stainless-steel brackets were bonded to the specimens (using Transbond XT), and SBS testing was performed. Data were analyzed by three-way ANOVA and LSD post-hoc tests (α = 0.05). Failure types were classified with adhesive remnant index (ARI) scores. Results: SBS values ranged from 1.5 to 14.9 MPa. Sandblasted bis-acryl and sandblasted auto-curing PMMA groups presented similar values (p> 0.05), higher than the CAD/CAM material (p< 0.05), with or without TC. When thermocycled, pumiced bis-acryl showed higher SBS than pumiced acrylic (p= 0.005) and CAD/CAM materials (p= 0.000), with statistical difference (p= 0.009). TC showed negative effect (p< 0.05) for sandblasted bis-acryl and pumiced acrylic groups. ARI predominant score was mostly zero (0) for CAD/CAM, 1 and 2 for bis-acryl, and 1 for acrylic groups. Conclusion: In general, bis-acryl material showed the highest SBS values, followed by acrylic and CAD/CAM materials, which showed SBS values lower than an optimum strength for bonding brackets.